Development of student leadership skills and identity : a case study at a Finnish university - Jensen, Jae (2017)
The modern world is constantly changing and presents new challenges to individuals entering professional and adult life. Many scholars recognize that leadership skills are a crucial tool for solving problems in all areas of society.Leadership is no longer believed to be an inborn trait, but rather something that can be taught and learned. This thesis aims to understand how students at the University of Jyväskylä assess their own leadership skills and their importance. It would also like to discover which activities, organizations, courses and experiences influenced students’ leadership development and how. Ultimately, this thesis would like to highlight opportunities to promote student leadership development. Qualitative focus group discussions were held with a total of seven diverse students from the University of Jyväskylä from various departments, both international and domestic. The discussions were recorded and analyzed using qualitative content analysis to identify key themes relating to leadership. The results revealed more barriers to involvement in leadership activities for international students. Previous experiences, including prolonged work in a field related to studies, were found to be influential to leadership development and students with such experience were more likely to participate in leadership activities at university. Older peer role models are influential in recruiting students for leadership activities at the university. It was also found that students perceptions of the supportiveness of their departments varies greatly and is a factor in their involvement in leadership. Overall, students could benefit from reflective learning exercises to discuss their experiences in relation to leadership.